Protecting Indigenous Peoples’ Rights Amid Land Ownership Uncertainty in Nusantara Capital City Development - Chrisna Julia Anggita Sari; Muhammad Ahsin Lana (CV. Pustaka Parawali, 2025)
The legal challenges surrounding spatial planning in Indonesia have gained prominence, particularly with the development of the National Capital (IKN) and the implementation of the One Map Policy (Big Map Policy). This study investigates the discrepancies between legal frameworks and actual practices, emphasizing the protection of indigenous rights, land disputes, and uncertainties in land ownership status. The construction of IKN is anticipated to intensify agrarian conflicts due to inadequate regulations, limited community involvement, and ineffective dispute resolution mechanisms. By examining pertinent laws, including Law No. 3 of 2022 on the National Capital and Law No. 26 of 2007 on Spatial Planning, this research aims to establish a comprehensive legal framework to address these issues. The findings underscore the necessity for enhanced coordination among government agencies and improved enforcement of existing regulations to ensure fair land management and safeguard the rights of local communities. Furthermore, the study highlights the importance of addressing the complexities of land ownership, particularly concerning customary land and indigenous rights, which are not adequately covered by current regulations. Ultimately, this research contributes to the ongoing discourse on spatial law in Indonesia, advocating for a more equitable and sustainable approach to land use and development in the context of IKN and beyond. The study calls for a reevaluation of existing policies to better align them with the realities on the ground, ensuring that the interests of all stakeholders are considered in the planning and implementation processes.